Редок случај на конгенитална адренална хиперплазија асоцирана со хиперкортизолемија - Iskra Bitovska; Marija Ilijovska; Argjent Mucha; Biljana Todorova; Tatjana Bajraktarova Prosheva; Goce Hristov; Toso Plaseski (My University, 2022)
Introduction: Congenital adrenal hyperplasia (CAH) describes a group of autosomal recessive disorders characterized by enzyme deficiency in the steroidogenic pathways most commonly due to 21 hydroxylase deficiency.CAH is generally associated with decreased or absent production of cortisol, increased ACTH secretion and excessive production of adrenal androgens and progesterone, including 17OH progesterone. We report a rare case of CAH associated with hypercortisolism. Case report:A 40 years old woman was referred to the Endocrinology unit for management of infertility presented with oligomenorrhea,acne and hirsutism. She had previously been labelled as a case of PCOSy and had been placed on various types of medications such as hormonal therapy and spironolactone.The first laboratory findings showed elevated levels of cortisol, adrenal androgens and testosterone. 17OH progesterone was also increased. After the diagnosis of CAH multiple laboratory tests were made and the plasma cortisol appeared to be repeatedly elevated. Dexamethasone test showed partial supression. 24hour urine cortisol test, abdominal CT and MRI of the pituitary glandwere also performedand showed no pathological findings. The diagnosis of CAH due to 21 hydroxylase deficiency was confirmed with genetic studies that showed mutation in CYP21A2(I172N). The genotype was homozygous. Conclusion:As the pathophysiology is basically a defect in the biosynthesis of cortisol, one may not consider CAH in patients with hypercortisolism. Althought this is an extremely rare case, more attention should be paid to this condition in hyperandrogenic womeneven if cortisol levels are elevаted. Key words: CAH, hyperandrogenism, PCOSy, hypercortisolemia